A SYSTEMATIC ANALYSIS OF THE INFLUENCE OF ACCURACY AND EASE OF USE ON USER SATISFACTION IN ELECTRONIC MEDICAL RECORDS - Christina Wijaniputri; Kosasih (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2026)
The implementation of Electronic Medical Records (EMR) systems has transformed healthcare services, yet user satisfaction remains a critical factor for successful adoption. This study aims to systematically analyze the effects of system accuracy and ease of use on user satisfaction at Hospital X. A quantitative explanatory approach was employed, with data collected from 100 healthcare professionals using a structured questionnaire. Validity and reliability tests confirmed the suitability of the instrument. Classical assumption tests, including normality, multicollinearity, and heteroscedasticity, indicated that the data met regression requirements. Multiple linear regression analysis revealed that system accuracy (β = 0.502, p < 0.01) and ease of use (β = 0.398, p < 0.01) have significant positive effects on user satisfaction. The F-test confirmed the simultaneous significance of both variables, and the coefficient of determination (R² = 0.684) showed that 68.4% of user satisfaction can be explained by these factors. The study concludes that both accuracy and usability are essential for enhancing user satisfaction, with accuracy having a slightly stronger impact. Optimizing data reliability and interface usability is crucial for maximizing the benefits of EMR systems in healthcare settings.